Novel Dietary and Lifestyle Inflammation Scores Directly Associated with All-Cause, All-Cancer, and All-Cardiovascular Disease Mortality Risks Among Women - Li, Zhuoyun (J Nutr, 2021)
BACKGROUND: Exogenous exposures collectively may contribute to chronic, low-grade inflammation and increase risks for major chronic diseases and mortality. We previously developed, validated, and reported a novel, FFQ-based and lifestyle questionnaire–based, inflammation biomarker panel–weighted, predominantly whole foods–based 19-component dietary inflammation score (DIS) and 4-component lifestyle inflammation score (LIS; comprising physical activity, alcohol intake, BMI, and current smoking status). Both scores were more strongly associated with circulating biomarkers of inflammation in 3 populations than were previously reported dietary inflammation indices. Associations of the DIS and LIS with mortality risk have not been reported. OBJECTIVES: To investigate separate and joint associations of the DIS and LIS with all-cause, all-cancer, and cardiovascular disease (CVD) mortality risks in the prospective Iowa Women's Health Study (1986–2012; n = 33,155 women, ages 55–69 years, of whom 17,431 died during follow-up, including 4379 from cancer and 6574 from CVD). METHODS: We summed each study participant's scores’ components, weighted by their published weights, to yield the participant's inflammation score; a higher score was considered more pro-inflammatory. We assessed DIS and LIS mortality associations using multivariable Cox proportional hazards regression. RESULTS: Among participants in the highest relative to the lowest DIS and LIS quintiles, the adjusted HRs for all-cause mortality were 1.11 (95% CI: 1.05–1.16) and 1.60 (95% CI: 1.53–1.68), respectively; for all-cancer mortality were 1.07 (95% CI: 0.97–1.17) and 1.51 (95% CI: 1.38–1.66), respectively; and for CVD mortality were 1.12 (95% CI: 1.03–1.21) and 1.79 (95% CI: 1.66–1.94), respectively (all P(trend) values < 0.01). Among those in the highest relative to the lowest joint LIS/DIS quintiles, the HRs for all-cause, all-cancer, and all-CVD mortality were 1.88 (95% CI: 1.71–2.08), 1.82 (95% CI: 1.50–2.20), and 1.92 (95% CI: 1.64–2.24), respectively. CONCLUSIONS: More pro-inflammatory diets and lifestyles, separately but especially jointly, may be associated with higher all-cause, all-cancer, and all-CVD mortality risks among women.